2006
DOI: 10.1017/s0020743806412265
|View full text |Cite
|
Sign up to set email alerts
|

The Saudi Public Speaks: Religion, Gender, and Politics

Abstract: The fact that fifteen of the nineteen terrorists who attacked the World Trade Center and the Pentagon on 11 September 2001 were Saudi citizens inevitably raised serious questions about the social conditions that have produced such violent personalities capable of the mass taking of innocent lives and devastating an entire city, if not a nation. Answers were quick to come by, as the U.S. media pointed to the Saudi culture. Charges were made that the youth were brainwashed by the most extremist school in Islam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 5 publications
1
34
2
Order By: Relevance
“…12, No. 5;2017 finds that both genders display transformational behaviours, and followers prefer to work with transformational leaders (Al-Ammaj, 2001, Walker, 2004, Omer, 2005, experience human relationships with their immediate leaders (Assad, 2006) and express favourable attitudes toward democracy (Moaddel, 2006). However, this study was conducted in a single-sex environment.…”
Section: Gender Similarity: Gender Roles In the Work Environmentmentioning
confidence: 93%
“…12, No. 5;2017 finds that both genders display transformational behaviours, and followers prefer to work with transformational leaders (Al-Ammaj, 2001, Walker, 2004, Omer, 2005, experience human relationships with their immediate leaders (Assad, 2006) and express favourable attitudes toward democracy (Moaddel, 2006). However, this study was conducted in a single-sex environment.…”
Section: Gender Similarity: Gender Roles In the Work Environmentmentioning
confidence: 93%
“…Despite the undemocratic regimes found in many of them, scholars have consistently observed that most citizens, even the staunchly religious, steadfastly advocate democracy as the best form of government in Muslim nations (e.g., Egypt, Jordan, Algeria, Morocco, Turkey, Pakistan, Bangladesh, and Saudi Arabia). The extent of identification among a country's populace with Islamic religion and culture does not seem to be a barrier to the democratization process (Al‐Braizat ; Moaddel ; Tessler ). A review of the history of Pakistan, for example, shows that although it is a Muslim state, it reformed its Muslim Personal Law and introduced several important changes for women, such as raising the minimum age of marriage.…”
Section: Religious Communities and The Statementioning
confidence: 99%
“…The cradle of Islam and an energy superpower, the Kingdom of Saudi Arabia is ruled by the Al‐Sa‘ud royal family whose reign is religiously sanctioned by the Al‐Shaykh family of clerics (Abukhalil, 2003; Al‐Rasheed, 2002). The seat of power represented by the Al‐Sa‘ud‐Al‐Shaykh alliance remained relatively unchallenged until the 1970s when a rapid growth in oil wealth and urbanization spawned various political formations, two of which contested prevailing political arrangements (Al‐Rasheed, 2007; Moaddel, 2006), especially after the upheaval brought by the 1991 Gulf War and the stationing of American troops on Saudi soil. On the one hand, Sahwi Islamists ( sahwa means “awakening”) believed Saudi Arabia to be insufficiently Islamic and accused establishment clerics of selling out to the royal family (Al‐Rasheed, 2002; Fandy, 1999).…”
Section: Saudi Politics and The Arab Media Revolutionmentioning
confidence: 99%
“…Partial answers reside in recent surveys that found the Saudi public to be ambivalent about social issues (Moaddel, 2006; Rheault, 2007). Although “[r]eligion, women, and democracy are among the most contested categories in the intellectual debates about the future of the kingdom” (Moaddel, 2006, p. 92), 71% of Saudis, the survey reveals, are in favor of democracy and 59% agree that a working mother can establish as warm a relationship with her children as a stay‐at‐home mother. In contrast, 23% of Saudis disagreed that men make better political leaders than women and 81% of Saudis agreed that a woman must always obey her husband.…”
Section: Neither Liberal Nor Conservative? the Ambivalence Of The Saumentioning
confidence: 99%
See 1 more Smart Citation